Exploring natural products-based cancer therapeutics derived from egyptian flora - El-Seedi, Hesham; Yosri, Nermeen; Khalifa, Shaden Ali M.; Guo, Zhiming; Musharraf, Syed Ghulam; Xiao, Jianbo; Saeed, Aamer; Du, Ming; Khatib, Alfi; Abdel-Daim, Mohamed M.; Efferth, Thomas; Göransson, Ulf; et al. (Elsevier, 2021)
Ethnopharmacological relevance: Egyptian plants are a rich source of natural molecules, representing considerable biodiversity due to climate variations between the Northern, Southern, Eastern and Western regions of the country. Sinai is considered a precious nature reserves preserving flora, fauna, marine organisms, and historical habitats with ancient origins. Here, traditional medicinal approaches have been used for hundreds of years. Healthy lifestyles, low levels of stress and microbial infections, and a dependence on flora and herbal medicine might in combination explain why the burden of cancer is lower in some regions than in others. Aim of the study: The primary aim of this review is to document the plants and natural products that are used as foods and medicines in Egypt, in general, and in Sinai, in particular, with a focus on those with demonstrated anticancer activities. The documented traditional uses of these plants are described, together with their chemical and pharmacological activities and the reported outcomes of clinical trials against cancer. Materials and methods: A literature search was performed to identify texts describing the medicinal plants that are cultivated and grown in Egypt, including information found in textbooks, published articles, the plant list website (http://www.theplantlist.org/), the medicinal plant names services website (http://mpns.kew.org/mpns-portal/), and web databases (PubMed, Science Direct, and Google Scholar). Results and discussion: We collected data for most of the plants cultivated or grown in Egypt that have been previously investigated for anticancer effects and reported their identified bioactive elements. Several plant species, belonging to different families and associated with 67 bioactive compounds, were investigated as potential anticancer agents (in vitro studies). The most potent cytotoxic activities were identified for the families Asteraceae, Lamiaceae, Chenopodiaceae, Apocynaceae, Asclepiadaceae, Euphorbiaceae, Gramineae, and Liliaceae. The anticancer activities of some species, such as Punica granatum L., Nerium oleander L., Olea europea L., Matricaria chamomilla L., Cassia acutifolia L., Nigella sativa L., Capsicum frutescens L., Withania somnifera L., and ingiber officinale Roscoe, have been examined in clinical trials. Among the various Egyptian plant habitats, we found that most of these plants are grown in the North Sinai, New-Delta, and Giza Governorates. Conclusion: In this review, we highlight the role played by Egyptian flora in current medicinal therapies and the possibility that these plants may be examined in further studies for the development of anticancer drugs. These bioactive plant extracts form the basis for the isolation of phytochemicals with demonstrated anticancer activities. Some active components derived from these plants have been applied to preclinical and clinical settings, including resveratrol, quercetin, isoquercetin, and rutin.